Glucometabolic reprogramming: From trigger to therapeutic target in hepatocellular carcinoma - Xia, Haoming; Huang, Ziyue; Wang, Zhensheng; Liu, Shuqiang; Zhao, Xudong; You, Junqi; Xu, Yi; Yam, Judy Wai Ping; Cui, Yunfu (Frontiers in Oncology, 2022)
Glucose, the central macronutrient, releases energy as ATP through carbon bond oxidation and supports various physiological functions of living organisms. Hepatocarcinogenesis relies on bioenergetic advantage conferred by glucometabolic reprogramming. The exploitation of reformed metabolism induces a uniquely inert environment conducive to survival and renders the hepatocellular carcinoma (HCC) cells the extraordinary ability to thrive even in the nutrient-poor tumor microenvironment. The rewired metabolism also confers a defensive barrier which protects the HCC cells from environmental stress and immune surveillance. Additionally, targeted interventions against key players of HCC metabolic and signaling pathways provide promising prospects of tumor therapy. The active search for novel drugs based on innovative mutation targets is warranted in the future for effectively treating advanced HCC and the preoperative downstage. This article aims to review the regulatory mechanisms and therapeutic value of glucometabolic reprogramming on the disease progression of HCC, to gain insights into basic and clinical research.